A tool for screening potentially inappropriate prescribing in Chinese children - Li, Siyu; Huang, Liang; Zeng, Linan; Yu, Dan; Jia, Zhi-Jun; Cheng, Guo; Zhang, Lingli (Frontiers in Pharmacology, 2022)
ABSTRACT Background: More than half of adverse drug events in pediatric inpatients are avoidable and blocking medication errors at the prescribing stage might be one of the most effective preventive measures. Objective: To form the criteria for detecting potentially inappropriate prescriptions in children, promote clinical rational drug use and reduce risks of medication in children. Methods: Potentially inappropriate prescription items for children were collected through a systematic review. Then, the Delphi technique was adopted to form the final criteria. Panelists were asked to use a 5-point Likert scale to rate their agreement with each potentially inappropriate prescription item and were encouraged to add new items based on their clinical experience and knowledge. After 2 round Delphi survey method and items were fully revised and improved, the final criteria for identifying potentially inappropriate prescriptions in children were formed. Results: The final criteria for identifying potential inappropriate prescriptions in children has 136 items, which were divided into “criteria for children with non-specific diseases/conditions” (71 items: 68 about potentially inappropriate medication, 3 about potential prescribing omission) and “criteria for children with specific diseases/conditions” (65 items: 55 about potentially inappropriate medication, 10 about potential prescribing omission), according to whether the item for identifying only potentially inappropriate prescriptions in children with specific diseases or conditions. Conclusion: A tool for screening potentially inappropriate prescriptions in children is formed to detect potentially inappropriate medication and prescribing omission in pediatrics and is available to all medical professionals liable to prescribe or dispense medication to children.